The Frankliniella curiosa spedes group (Thysanoptera: Tbripidae) - Johansen, Roberto M (Universidad de Costa Rica, 1998)
Ihis is a review of the Mexican species Frankliniella curiosa Priesner, together with the description of eight new Mexican related species. Ihe outstanding morphology of antennal segment III in the adults, with a ventral projected and curved beak (which covers the pedicel), is an exclusive and typical character, which allows their separation into a new and different species group in !he genus . Sorne other morphological characters divide the group in four species assemblages. Illustrations of!he head, antennae, thorax and abdomen of each species are included.